Endothelial function is impaired in the cutaneous microcirculation of adults with psoriasis through reductions in nitric oxide-dependent vasodilation - Alba, Billie K.; Greaney, Jody L.; Ferguson, Sara B.; Alexander, Lacy M. (American journal of physiology. Heart and circulatory physiology, 2018)
Psoriasis is an independent risk factor for cardiovascular disease; however, the underlying mechanisms are not fully understood. Deficits in conduit arterial function are evident in patients with psoriasis, but potential impairments in microcirculatory endothelial function remain unclear. We hypothesized that cutaneous microvascular dysfunction would be detectable in otherwise healthy individuals with psoriasis. Two intradermal microdialysis fibers were placed in (nonlesional) forearm skin of nine patients (3 men and 6 women, 39 ± 5 yr) with moderate (16 ± 2% of body surface area) plaque psoriasis and nine healthy (nonpsoriatic) control subjects (3 men and 6 women, 38 ± 5 yr) for local delivery of 1) lactated Ringer solution (control) and 2) 10 mM l-ascorbate (a nonspecific antioxidant). An index of skin blood flow was measured using laser-Doppler flowmetry during local heating (42°C). Nitric oxide (NO)-dependent vasodilation was directly quantified after perfusion of the nonspecific NO synthase inhibitor N G -nitro-l-arginine methyl ester (15 mM). A third fiber was perfused with increasing concentrations (10 −10 – 10 −2 M) of norepinephrine to elicit adrenoreceptor-mediated cutaneous vasoconstriction. NO-dependent vasodilation was attenuated in patients with psoriasis (57 ± 5% and 39 ± 7% maximum cutaneous vascular conductance in control subjects and adults with psoriasis, respectively, P < 0.01). l-Ascorbate did not improve NO-dependent vasodilation ( P > 0.05). There was no group difference in maximal vasoconstriction or microvascular sensitivity to norepinephrine ( P > 0.05). These data suggest that NO bioavailability is reduced in otherwise healthy individuals with psoriasis, which contributes to systemic microvascular dysfunction. NEW & NOTEWORTHY In adults with psoriasis, reduced nitric oxide bioavailability mediates impaired endothelium-dependent vasodilation, independent of increases in oxidative stress. Furthermore, the degree of psoriatic symptomology is directly related to greater reductions in nitric oxide-dependent vasodilation.